The Relationship Between Abdominal Muscle Strength and Arm Muscle Strength with the Ability to Throw the Ball Inside in a Football Game - Bismar, Ahmad Rum; Amahoru, Nurul Musfira (Sains Global Institut, Indonesia, 2024)
This study aims to determine the relationship between abdominal muscle strength and arm muscle strength with the ability to throw the ball inward in the football game of SMP Negeri 2 Makassar students. This research is a type of descriptive research. The population of this study is all students of SMP Negeri 2 Makassar with a research sample of 60 male students selected by random sampling. The data analysis technique used is a correlation analysis technique using the SPSS Version 20.00 system at a significant level of 95% or = 0.05. Based on the results of data analysis, this study concludes that: There is a significant relationship between abdominal muscle strength and the ability to throw the ball inward in a football game, (ro = 0.841 with a probability level of (0.000) <  = 0.05); There was a significant relationship between arm muscle strength and the ability to throw the ball inward in the game of football, (ro = 0.778 with the probability of (0.000) <  = 0.05); There was a significant relationship between the strength of the abdominal muscles and the strength of the arm muscles and the ability to throw the ball in the game of soccer (Ro = 0.866 with the probability level of (0.000) <  = 0.05).